HUBUNGAN BPMPTSP DENGAN DINAS PERTAMBANGAN DAN ENERGI DALAM PENERBITAN IZIN TAMBANG GALIAN C - MULYA NINGSI KATILI (Universitas Muhammadiyah Semarang, 2017)
Research aims to review determine Relationships authority Yang formed Investment Board and One Stop WITH Mining and Energy hearts Issuance of Permits quarry C and the extent of the relationship of such authority CAN creates Licensing Services The Quick, Easy, Cheap and berkepastian law in the District Gorontalo.The study conducted in Board of Investment and Integrated Services One Stop WITH Department of Mines and Energy in Gorontalo Regency for a review of field research, and Library Faculty of Law, University of Muhammadiyah Gorontalo to review the research literature. Methods What the author is a method of research literature, Research Singer Writers do WITH reading As well as reviewing different literature Relevant and deal directly with the object Research Yang serve as the theoretical foundation, in addition to ITU Writer Also do Research Methods Courses, conducted WITH How to Interview OR talks Jump Openhearts and debriefing Form WITH resource.Output TIN Writer hearts Research is: (1) In Relation authority and Investment Agency One Stop WITH Department of Mines and Energy in the district of Gorontalo, which is authorized to review the issue a permit mine Excavation C it is a Board of Investment and Integrated Services One door, but hearts Resolution process permission Mining and Energy Department through the Technical Committee has the authority to review approve OR NOT agree to permit Yang in beg by the applicant as a recommendation to the head BPMPTSP shown. (2) Since the establishment of the Investment and One Stop in Gorontalo district by decree No. 4 of 2007 REGARDING organization and working procedures BPMPTSP And, process of obtaining a License in Gorontalo Regency MORE Being fast, and cheap. Misalnya hearts Issuance of Permits quarry C. The first, The governing IN Mining and Energy reaches 10 working days now shown to BPMPTSP dilimpahkannya WITH WITH THE collaborated Fixed Related Department settlement fence Slow Just Around 7 days only and is NOT in pick levy Licensing. Keywords: Publishing and Licensing, Mining and quarrying c, BPMPTSP WITH Mining and energy, Gorontalo Regency.